2017
DOI: 10.11152/mu-933
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Doppler in musculoskeletal ultrasonography – suboptimal performance of both experienced and in-training sonographers in selection of the highest Doppler signal image from cine-loops

Abstract: Aims: Doppler ultrasonography assessment is mandatory nowadays for the complete description of rheumatic disease activity. Initially it was performed in semi quantitative way but recently the (fully) quantitative assessment is gaining more interest. In quantitative assessment, the ratio between total colorized and total pixels (CTR) is computed for the whole image or just for the region of interest (ROI). The frame with the highest amount of Doppler signal (also called worst case scenario image – WCSI) is usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…However, some studies have found that text clues increase cognitive education. Berghea investigated the impact of text cues on the cognitive education of graphics processing in a virtual environment [4]. Cognitive education research is inseparable from the investigation of individual working memory.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have found that text clues increase cognitive education. Berghea investigated the impact of text cues on the cognitive education of graphics processing in a virtual environment [4]. Cognitive education research is inseparable from the investigation of individual working memory.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of evaluating conventional and targeted therapies in rheumatic diseases are limited and the reported results are often variable. Musculoskeletal ultrasonography and synovial biopsies could not correctly evaluate the effects of the applied therapies, which is why the use of other diagnostic methods and therapeutic evaluation tools are required in rheumatoid arthritis (RA) and psoriatic arthritis (PsA) (14). Changes in the skin induced by RA or PsA are scarcely studied (15,16).…”
mentioning
confidence: 99%